A Systematic Review on Integrating MALL in English Language Teaching - Sahril Nur; Ranta Butarbutar; Sri Yulianti Ardiningtyas; Andi Haeriati Alimuddin (ELT Worldwide: Journal of English Language Teaching, 2022)
The use of technology in language learning has been going on for a long time. Many technological characteristics are currently utilized in language learning as a result of the rapid growth of technology. MALL is one of them. This study aims to review integrating MALL in English language teaching (ELT). The study employed a systematic review checklist as a method. Findings suggest that MALL has a good impact on students' English language development, which leads to positive outcomes, according to the overall findings. Parents, teachers, and students expressed an interest in promoting MALL in ELT. Teachers were enthusiastic about MALL and felt that it could be utilized to teach English. MALL also had a positive influence in educational contexts, with students enthusiastic about utilizing it in English classes. They also believe that MALL provides them with numerous benefits when performing their tasks. Due to the challenges teachers and students encounter in applying and using MALL in ELT, such as psychological, pedagogical, and technical limits, stakeholders are expected to develop solutions and policies to achieve effective technology-oriented learning in ELT.  Keywords: Systematic review, MALL, ELT